Bridging Cultures: Explorations, Collisions + Considerations of Indigeneity & Design (EAAE Joint Publishings, 2026)
This research project addresses a long-standing issue in contemporary Environmental design education and practice: the exclusion of Indigenous perspectives in all educational processes, principles, and policies. This one-year research initiative collaborated with three Indigenous Knowledge Keepers as guides and mentors and aimed at integrating indigenous ways of seeing and knowing into curricula and pedagogy within the fields of Architecture, Planning, and Landscape. The initiative was funded by an Indigenous Engagement Grant from the University of Calgary and spanned two consecutive semesters, involving multiple studios and courses, where instructors had the flexibility and support to align their course content with the overarching Indigenous research theme. Roundtable discussions and workshops, led by Indigenous leaders, played a pivotal role in the project. These workshops served various purposes throughout the academic year, including introducing Indigenous Culture, providing design critiques, offering reflections, and allowing for open question sessions. Key to this endeavor's success was the creation of a welcoming and respectful environment. The research recognized the need to treat Western Design and Indigenous cultures as distinct, running in parallel, with the establishment of an ethical space as a secure and safe bridge between them. In bringing Design and Indigenous realms into juxtaposition, and at times collision, the research leaders needed to be supportive and diligent around risks & vulnerabilities, while cultivating opportunities and opening doors to discovery. Despite the participants’ initial lack of awareness about Indigenous ways, the guidance of Indigenous mentors, coupled with facilitation by research leaders and participant motivation, led to significant progress in design work that incorporated, respected, and celebrated Indigenous knowledge. This paper narrates the educational journey of this initiative and outlines valuable lessons that promise to positively impact the design education and practice of tomorrow.